Maximum Torque per Ampere Control of Permanent Magnet Synchronous Motor Using Genetic Algorithm - Farzad Tahami; Hamed Nademi; Mohammad Rezaei (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Permanent magnet synchronous motor (PMSM) drives have many advantages over other drives, i.e. high efficiency and high power density. Particularly, PMSMs are epoch-making and are intensively studied among researchers, scientists and engineers. This paper deals with a novel high performance controller based on genetic algorithm. The scheme allows the motor to be driven with maximum torque per ampere characteristic. In this paper assuming an appropriate fitness function, the optimum values for d-axis current of motor set points at each time are found and then applied to the controller. Simulation results show the successful operation of the proposed controller.